Torn asunder - Ross, Barbara, 1953- (Kensington Cozies, 2024)
Julia's best friend and business partner, Zoey, is about to marry her policeman boyfriend. Of course, a gorgeous white wedding dress shouldn't be within fifty yards of a plate of buttery lobster--so that treat is reserved for the rehearsal dinner. Julia is a little worried about the timing, though, as she works around a predicted storm. When a guest falls to the floor dead, it turns out that no one seems to know who he is, despite the fact that he's been actively mingling and handing out business cards. And when an injection mark is spotted on his neck, it's clear this wasn't caused by a shellfish allergy. Now, as the weather deteriorates and a small group is stranded on the island with the body--and the killer--Julia starts interrogating staff, family members, and Zoey's artist friends to find out who turned the clambake into a crime scene... --